Технологія отримання декарбанізованого моторного палива - Чернявський, Андрій Володимирович; Григоров, Андрій Борисович (Національний університет "Львівська політехніка", 2023)
The technology that allows to obtain partially decarbonized motor fuel is presented. This technology is implemented by two-stage catalytic pyrolysis, with pyrolysis and synthesis reactions taking place at the first stage of the process, and hydrogenation of the obtained products at the second stage. By implementing this technology, a fraction of 180-360(380) °C was obtained on Zn-H-ZSM-5/Fe-H-ZSM-5, Ni-H-ZSM-5 catalysts from secondary polymer raw materials (HDPE and PP) with the H:C ratio at the level of 1.62-1.64.
Keywords: декарбанізоване моторне паливо; декарбонізація промисловості; отримання морського палива; полімерна сировина; поліетилен високої густини